1369. Oritavancin Activity Against Methicillin-Resistant S. aureus (MRSA) Isolates Causing Skin and Skin Structure Infections in US Hospitals (2017-2019). (4th December 2021) - Carvalhaes, Cecilia G; Sader, Helio S; Shortridge, Dee; Streit, Jennifer M; Mendes, Rodrigo E
Abstract: Background: MRSA remains an important cause of community-onset (CA) and nosocomial (NA)- SSSI. Oritavancin (ORI) is a lipoglycopeptide antibiotic with activity against S. aureus, including MRSA and multidrug-resistant (MDR) strains. ORI was approved for clinical use by the US FDA to treat ABSSSI with a single 1, 200 mg infusion over 1 (Kimyrsa) or 3 (Orbactiv) hours. This study evaluated the activity of ORI against MRSA isolates causing SSSI from US medical centers. Methods: A total of 3, 792 S. aureus isolates were consecutively collected (1 per patient) from 31 medical centers in 2017-2019 and tested for susceptibility (S) to ORI and comparators using CLSI broth microdilution methods. Among 1, 582 (41.7%) MRSA isolates, 1, 379 (87.2%) were reported as CA-MRSA and 203 (12.8%) as NA-MRSA. CA-MRSA isolates were evaluated by resistance (R) subgroups, including clindamycin (CLI-R; n=283; 20.5%), levofloxacin (LEV-R; n=831; 60.3%), MDR (non-susceptible to ≥3 classes of agents; n=816; 59.2%), and extensively drug resistant (XDR; non-susceptible to ≥5 classes; n=47; 3.4%). Results: Overall, ORI inhibited 99.9% of all S. aureus isolates at the susceptible breakpoint (≤0.12 mg/L; 99.9% of MSSA and 100% of MRSA; Table). S rates were generally comparable between NA-MRSA and CA-MRSA isolates for ORI (100%S) and linezolid (LZD, 100%S) but lower susceptibility was observed for NA-MRSA compared to CA-MRSA for CLI (71.9%S vs. 79.1%S), LEV (31.0%S vs. 39.4%S), and trimethoprim-sulfamethoxazole (TMP-SMX; 91.1%S vs. 96.9%S). ORI was active against MRSA (MIC50/90, 0.03/0.03 mg/L), regardless of infection status (NA, MIC50/90, 0.03/0.06 mg/L; CA, MIC50/90, 0.03/0.03 mg/L). ORI and LZD remained active (100%S) against all CA-MRSA subsets: CLI-R, LEV-R, MDR, and XDR. Limited activity of CLI (69.9%S) and LEV (13.1%S) was observed against MRSA and each R subset, whereas TMP-SMX had >90%S for all MSSA, MRSA, and R subsets, except XDR. Conclusion: ORI exhibited potent in vitro activity against MRSA, regardless of the infection onset or R subset, in contrast to many comparators that lack activity against both, CA-MRSA and NA-MRSA. This in vitro activity, combined with the infusion time options provided to clinicians, suggests ORI is a favorable agent for treating SSSI in the US caused by MRSA, including MDR and XDR strains. Disclosures: Cecilia G. Carvalhaes, MD, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)Cidara Therapeutics, Inc. (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Pfizer, Inc. (Research Grant or Support) Helio S. Sader, MD, PhD, FIDSA, AbbVie (formerly Allergan ) (Research Grant or Support)Basilea Pharmaceutica International, Ltd. (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)Department of Health and Human Services (Research Grant or Support, Contract no. HHSO100201600002C)Melinta Therapeutics, LLC (Research Grant or Support)Nabriva Therapeutics (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Dee Shortridge, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Shionogi (Research Grant or Support) Jennifer M. Streit, BS, GlaxoSmithKline, LLC (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Rodrigo E. Mendes, PhD, AbbVie (Research Grant or Support)AbbVie (formerly Allergan ) (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)ContraFect Corporation (Research Grant or Support)GlaxoSmithKline, LLC (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Nabriva Therapeutics (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support)